Of mice and men: Pinpointing species differences in adipose tissue biology - Börgeson, Emma; Boucher, Jeremie; Hagberg, Carolina E. (Frontiers in Cell and Developmental Biology, 2022)
The prevalence of obesity and metabolic diseases continues to rise, which has led to an increased interest in studying adipose tissue to elucidate underlying disease mechanisms. The use of genetic mouse models has been critical for understanding the role of specific genes for adipose tissue function and the tissue’s impact on other organs. However, mouse adipose tissue displays key differences to human fat, which has led, in some cases, to the emergence of some confounding concepts in the adipose field. Such differences include the depot-specific characteristics of visceral and subcutaneous fat, and divergences in thermogenic fat phenotype between the species. Adipose tissue characteristics may therefore not always be directly compared between species, which is important to consider when setting up new studies or interpreting results. This mini review outlines our current knowledge about the cell biological differences between human and mouse adipocytes and fat depots, highlighting some examples where inadequate knowledge of species-specific differences can lead to confounding results, and presenting plausible anatomic explanations that may underlie the differences. The article thus provides critical insights and guidance for researchers working primarily with only human or mouse fat tissue, and may contribute to new ideas or concepts in the important and evolving field of adipose biology.